Review on Face Detection and Recognition Technology Based on Neural Network - Yadav, Abhishek; Mahajan, Sachin (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2017)
In this paper, feature extraction and facial recognition are studied in order to resolve problems like highdimension problem, small size samples and no-linear separable problem that exist in facial recognition technology. In the part of feature extraction we use a HGPP algorithm, to extract the input features in building a face recognition system. The neural network, which represents brilliant performance on small training sets, non-linear separable and high-dimension pattern recognition problems in the recognition stage, is used for pattern classification. The proposed approach is validated with the ORL database. Experimental results demonstrate the effectiveness of this method in the performance of face recognition.